2020
DOI: 10.3233/cbm-201595
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones concentration in portal and peripheral blood in patients with pancreatic cancer: Preliminary study

Abstract: BACKGROUND: The prognostic value of D-dimers concentration in portal blood in patients with pancreatic cancer has been established in several studies. Thyroid hormones and their receptors, especially T3 also seems to have a specific role in process of neoplasia and metastatic spread. OBJECTIVE: The aim of the study was to look for changes of thyroid hormones concentration between portal and peripheral blood. METHODS: We included prospectively 8 patients with pancreatic cancer, without liver dysfunction, qualif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…In humans, D-dimer portal concentration is proved to be higher than peripheral when comparing PDAC patients to those with benign pancreatic diseases [ 7 , 15 , 16 , 17 , 18 ]. Furthermore, in the pilot study on a small group of PDAC patients, the fT3 change coefficient (peripheral to portal blood) showed a strong statistically significant negative correlation with the portal D-dimer concentration level [ 14 ], which is in line with Durczynski et al These results allude to the existence of multiple, multidirectional, mutual bindings between cancer culture, hormonal balance, and coagulation profile. Although the influence of neoplastic disease on the body’s hormonal balance is widely recognized, it is also highly knotty.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In humans, D-dimer portal concentration is proved to be higher than peripheral when comparing PDAC patients to those with benign pancreatic diseases [ 7 , 15 , 16 , 17 , 18 ]. Furthermore, in the pilot study on a small group of PDAC patients, the fT3 change coefficient (peripheral to portal blood) showed a strong statistically significant negative correlation with the portal D-dimer concentration level [ 14 ], which is in line with Durczynski et al These results allude to the existence of multiple, multidirectional, mutual bindings between cancer culture, hormonal balance, and coagulation profile. Although the influence of neoplastic disease on the body’s hormonal balance is widely recognized, it is also highly knotty.…”
Section: Discussionsupporting
confidence: 60%
“…Directly influencing the coagulation profile, especially in the portal blood, is fairly common; however, potentially disturbing the interpretation of this study results in tissue factor (TF) overexpression on the tumor cells [ 13 ]. One of its effects is well described by our D-dimer group with a high concentration in portal blood [ 7 , 14 , 15 , 16 , 17 , 18 ]; however, the other can shorten the aPTT and raise the level of fibrinogen concentration ( Figure 2 ). Our study proved that another haemostatic marker for hypercoagulability, i.e., shortened aPTT, may also help to distinguish between different types of pancreatic tumors in males.…”
Section: Discussionmentioning
confidence: 82%
“…In TN breast cancer, fT3 may be involved in the transduction of proliferation signals 14 . Strzałka A et al found that fT3 also contributes to the development of pancreatic cancer 15 . Therefore, the predictive effect of fT3 on the recurrence of PTC should be explored further.…”
Section: Resultsmentioning
confidence: 99%
“…Strzałka A et al found that fT3 also contributes to the development of pancreatic cancer 15 . Therefore, the predictive effect of fT3 on the recurrence of PTC should be explored further.…”
Section: Effects Of Tsh and Thyroid Hormone On Ptc Recurrencementioning
confidence: 99%